Monogenic familial autoinflammatory Behçet-like syndrome/ haploinsufficiency A20 syndrome is a new form of autoinflammatory pathology. Literature review and description of cases - Е. S. Fedorov; S. О. Salugina; Е. Yu. Zakharova; А. N. Shapovalenko; S. G. Radenska-Lopovok; V. G. Matkava; А. N. Arefieva (Научно-практическая ревматология)
Monogenic familial autoinflammatory Behçet-like syndrome/haploinsufficiency A20 syndrome is a hereditary autoinflammatory disease from the group of ubiquitinopathies which are caused by a mutation of the TNFAIP3 gene encoding the A20 protein with an autosomal dominant inheritance mechanism and clinical picture similar to Behçet’s disease. Pathogenesis is based on a 50% function decreasing of the nuclear factor inhibitor protein NFkB, what leads to overexpression of proinflammatory cytokines. The disease onset is usually in childhood. Clinical features are presented with recurrent aphthous stomatitis and genital aphthae in most patients and also inflammatory bowel damage is noted. Eye damage is noted rarely than in sporadic Behçet’s disease. In addition, the clinical picture may be presented with arthritis, skin rashes, lesions of the cardiovascular system (pericarditis), fever. Increasing of acute-phase markers is noticed, there is a high frequency of autoantibodies detection in contrast with “classic” autoinflammattory diseases. It can be combined with other autoimmune diseases (systemic lupus erythematosus (SLE), autoimmune thyroiditis, hepatitis, etc.). The description of two patients and comparison with another patient from Russia who was described earlier are presented. All patients had aphthous stomatitis and genital aphthaes, intestinal inflammation symptoms, which was dominanting in one of the patients. Another patient had severe polyarthritis in combination with immunological manifestations which were typical for SLE. The first patient had a good clinical response with the tumor necrosis factor inhibitor adalimumab, the second patient – the anti-B cell drug rituximab.